Kepler-15b: A hot jupiter enriched in heavy elements and the first kepler mission planet confirmed with the hobby-eberly telescope - Endl, Michael; Macqueen, Phillip J; Cochran, William D; Brugamyer, Erik; Buchhave, Lars A; Rowe, Jason F; Lucas, P W; Isaacson, Howard; Bryson, Steve; Howell, Steve B; Fortney, Jonathan J; Hansen, Terese; et al. (Astrophysical Journal Supplement Series, 2011)
We report the discovery of Kepler-15b (KOI-128), a new transiting exoplanet detected by NASA's Kepler mission. The transit signal with a period of 4.94days was detected in the quarter 1 (Q1) Kepler photometry. For the first time, we have used the High Resolution Spectrograph (HRS) at the Hobby-Eberly Telescope (HET) to determine the mass of a Kepler planet via precise radial velocity (RV) measurements. The 24 HET/HRS RVs and 6 additional measurements from the Fibre-fed chelle Spectrograph spectrograph at the Nordic Optical Telescope reveal a Doppler signal with the same period and phase as the transit ephemeris. We used one HET/HRS spectrum of Kepler-15 taken without the iodine cell to determine accurate stellar parameters. The host star is a metal-rich ([Fe/H]= 0.36 ± 0.07) G-type main-sequence star with Teff = 5515 ± 124 K. The semi-amplitude K of the RV orbit is 78.7+8.5 -9.5ms-1, which yields a planet mass of 0.66 ± 0.1 M Jup. The planet has a radius of 0.96 ± 0.06R Jup and a mean bulk density of 0.9 ± 0.2 gcm-3. The radius of Kepler-15b is smaller than the majority of transiting planets with similar mass and irradiation level. This suggests that the planet is more enriched in heavy elements than most other transiting giant planets. For Kepler-15b we estimate a heavy element mass of 30-40 M ⊕. © 2011. The American Astronomical Society. All rights reserved.
23 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-839-775-387-264 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (Kepler-15; KOI-128; KIC 11359879; 2MASS J19444814+4908244); techniques: image processing; techniques: photometric; techniques: radial Velocities; techniques: spectroscopic

Transit timing observations from kepler: III. confirmation of 4 multiple planet systems by a fourier-domain study of anti-correlated transit timing variations - Steffen, Jason H.; Fabrycky, Daniel C.; Ford, Eric B.; Carter, Joshua A.; Désert, Jean-Michel; Fressin, Francois; Holman, Matthew J.; Lissauer, Jack J.; Moorhead, Althea V.; Rowe, Jason F.; Ragozzine, Darin; Welsh, William F.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
We present a method to confirm the planetary nature of objects in systems with multiple transiting exoplanet candidates. This method involves a Fourier-domain analysis of the deviations in the transit times from a constant period that result from dynamical interactions within the system. The combination of observed anticorrelations in the transit times and mass constraints from dynamical stability allow us to claim the discovery of four planetary systems, Kepler-25, Kepler-26, Kepler-27 and Kepler-28, containing eight planets and one additional planet candidate. © 2012 Fermi Research Alliance LLC, Contractor for the U.S. Dept of Energy Monthly Notices of the Royal Astronomical Society © 2012 RAS.
121 citations (Crossref) [2023-10-31] Citation Key Alias: pop00008 tex.type: [object Object]
Keywords: Celestial mechanics; Methods: data analysis; Stars: individual: KIC 4349452; Stars: individual: KIC 5792202; Stars: individual: KIC 6949607; Stars: individual: KIC 9757613; dept.phy; peer-reviewed

Transit timing observations from kepler. II. confirmation of two multiplanet systems via a non-parametric correlation analysis - Ford, Eric B.; Fabrycky, Daniel C.; Steffen, Jason H.; Carter, Joshua A.; Fressin, Francois; Holman, Matthew J.; Lissauer, Jack J.; Moorhead, Althea V.; Morehead, Robert C.; Ragozzine, Darin; Rowe, Jason F.; Welsh, William F.; et al. (The Astrophysical Journal, 2012)
We present a new method for confirming transiting planets based on the combination of transit timing variations (TTVs) and dynamical stability. Correlated TTVs provide evidence that the pair of bodies is in the same physical system. Orbital stability provides upper limits for the masses of the transiting companions that are in the planetary regime. This paper describes a non-parametric technique for quantifying the statistical significance of TTVs based on the correlation of two TTV data sets. We apply this method to an analysis of the TTVs of two stars with multiple transiting planet candidates identified by Kepler. We confirm four transiting planets in two multiple-planet systems based on their TTVs and the constraints imposed by dynamical stability. An additional three candidates in these same systems are not confirmed as planets, but are likely to be validated as real planets once further observations and analyses are possible. If all were confirmed, these systems would be near 4:6:9 and 2:4:6:9 period commensurabilities. Our results demonstrate that TTVs provide a powerful tool for confirming transiting planets, including low-mass planets and planets around faint stars for which Doppler follow-up is not practical with existing facilities. Continued Kepler observations will dramatically improve the constraints on the planet masses and orbits and provide sensitivity for detecting additional non-transiting planets. If Kepler observations were extended to eight years, then a similar analysis could likely confirm systems with multiple closely spaced, small transiting planets in or near the habitable zone of solar-type stars. © 2012. The American Astronomical Society. All rights reserved.
73 citations (Crossref) [2023-10-31] Citation Key Alias: pop00013 tex.type: [object Object]
Keywords: dept.phy; planetary systems; planets and satellites: detection; planets and satellites: dynamical evolution and stability; stars: individual (KIC 3231341; 11512246; KOI 168; 1102; Kepler-23; Kepler-24); techniques: miscellaneous

Kepler-14b: A Massive Hot Jupiter Transiting an F Star in a Close Visual Binary - Buchhave, Lars A; Latham, David W; Carter, Joshua A; Desert, J M; Torres, Guillermo; Adams, Elisabeth R; Bryson, Stephen T; Charbonneau, David; Ciardi, David R; Kulesa, Craig; Dupree, Andrea K; Fischer, Debra A; et al. (Astrophysical Journal Supplement Series, 2011)
We present the discovery of a hot Jupiter transiting an F star in a close visual (03 sky projected angular separation) binary system. The dilution of the host star's light by the nearly equalmagnitude stellar companion (∼0.5mag fainter) significantly affects the derived planetary parameters, and if left uncorrected, leads to an underestimate of the radius and mass of the planet by 10% and 60%, respectively. Other published exoplanets, which have not been observed with high-resolution imaging, could similarly have unresolved stellar companions and thus have incorrectly derived planetary parameters. Kepler-14b (KOI-98) has a period of P = 6.790 days and, correcting for the dilution, has a mass of Mp = 8.40+0.35 -0.34 M J and a radius of Rp = 1.136+0.073-0.054 R J, yielding a mean density of ρp = 7.1 ± 1.1 g cm-3. © 2011. The American Astronomical Society. All rights reserved.
52 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-747-569-084-362 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (Kepler-14b; KIC 10264660; 2MASS J19105011+4719589); techniques: photometric; techniques: spectroscopic

Kepler-22b: A 2.4 Earth-radius Planet in the Habitable Zone of a Sun-like Star - Borucki, William J.; Koch, David G.; Batalha, Natalie M.; Bryson, Stephen T.; Rowe, Jason F.; Fressin, Francois; Torres, Guillermo; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2012)
A search of the time-series photometry from NASA's Kepler spacecraft reveals a transiting planet candidate orbiting the 11th magnitude G5 dwarf KIC 10593626 with a period of 290 days. The characteristics of the host star are well constrained by high-resolution spectroscopy combined with an asteroseismic analysis of the Kepler photometry, leading to an estimated mass and radius of 0.970 0.060 M and 0.979 0.020 R. The depth of 492 10 ppm for the three observed transits yields a radius of 2.38 0.13 Re for the planet. The system passes a battery of tests for false positives, including reconnaissance spectroscopy, high-resolution imaging, and centroid motion. A full BLENDER analysis provides further validation of the planet interpretation by showing that contamination of the target by an eclipsing system would rarely mimic the observed shape of the transits. The final validation of the planet is provided by 16 radial velocities (RVs) obtained with the High Resolution Echelle Spectrometer on Keck I over a one-year span. Although the velocities do not lead to a reliable orbit and mass determination, they are able to constrain the mass to a 3σ upper limit of 124 M ⊕, safely in the regime of planetary masses, thus earning the designation Kepler-22b. The radiative equilibrium temperature is 262 K for a planet in Kepler-22b's orbit. Although there is no evidence that Kepler-22b is a rocky planet, it is the first confirmed planet with a measured radius to orbit in the habitable zone of any star other than the Sun. © 2012. The American Astronomical Society. All rights reserved.
186 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: fundamental parameters; stars: individual (Kepler-22; KIC 10593626)